2014
DOI: 10.1007/s00167-014-3416-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of open acromioplasty, arthroscopic acromioplasty and physiotherapy in patients with subacromial impingement syndrome: a prospective randomised study

Abstract: CT with low follow-up rate, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 36 publications
0
55
2
1
Order By: Relevance
“…For trials not reporting the index instrument, we followed a prespecified outcome hierarchy when deciding which data would be pooled (online supplementary appendix table 2). For Farfaras et al, 25 we combined 15 the open and arthroscopic subacromial decompression surgery arms in all analyses.…”
Section: Data Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…For trials not reporting the index instrument, we followed a prespecified outcome hierarchy when deciding which data would be pooled (online supplementary appendix table 2). For Farfaras et al, 25 we combined 15 the open and arthroscopic subacromial decompression surgery arms in all analyses.…”
Section: Data Managementmentioning
confidence: 99%
“…Both trials also included a non-surgical arm. Five trials 25 Review subacromial decompression surgery with exercise therapy; one had a placebo laser arm with no active treatment. 30 One trial 34 compared acromioplasty plus bursectomy with bursectomy alone.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, after excluding duplicate and obviously irrelevant reports, 20 articles were retained. By carefully reading the full text, it was found that: 3 articles 16-18 were just study protocol, 1 article 6 we couldn't extract the data we need, 2 article 19,20 were not randomized controlled trial, 3 articles [21][22][23] were based on the comparison of other surgical method and conservative management. 11 studies met our inclusion and exclusion criteria, and among these studies, 5 studies [24][25][26][27][28] published by Ketola et al described the same clinical study and the follow-up time of these studies all belonged to our long-term subgroup, so we only included as one.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%